Wear Behavior of Borided Cold-Rolled High Manganese Steel - Hayat, Fatih; Sezgin, Cihangir Tevfik (MDPI AG, 2021)
In this study, a novel high-manganese steel (HMS) was borided at 850, 900 and 950 °C for 2, 4, and 6 h by the pack boriding process. Contrary to previous literature, borided HMS uncommonly exhibited saw-tooth morphology like low alloy steels, and manganese enhanced the boron diffusion. Another striking analysis is that the “egg-shell effect” did not occur. The present study demonstrated the silicon-rich zone for the first time in the literature by EDX mapping. Moreover, the formation mechanism of silicon-rich zones was explained and termed as “compact transfer of silicones (CTS)”. XRD analysis showed the existence of FeB, Fe2B, MnB and SiC phases. The boriding time and temperature increased the thickness of the boride layer from 31.41 μm to 117.65 µm. The hardness of the borided layer ranged from 1120 to 1915 HV0.05. The activation energy of borided HMS was found to be a very low result compared to high alloy steel investigated in the literature. The Daimler-Benz Rockwell-C adhesion test showed that adhesions of borided HMS surfaces are sufficient. The dry sliding wear tests showed that boriding treatment increased the wear resistance of untreated HMS by 5 times. The present study revealed that the boriding process extended the service life of HMS components.
Keywords: wear; high manganese steel; adhesion test; diffusion kinetic; boriding